Use of the BacT/Alert MB Mycobacterial Blood Culture System for Detection of Mycobacteria in Sterile Body Fluids Other than Blood - Mattei, Romano (American Society for Microbiology (ASM), 2009)
The definitive diagnosis of extrapulmonary tuberculosis is made by a positive body fluid culture result. Conventional culture methods require centrifugation or filtration of body fluid (peritoneal, pleural, synovial, or pericardial fluid) in order to improve the sensitivity. The aim of the present study was to evaluate the feasibility of the direct inoculation, at the patient's bedside, of up to 5 ml of uncentrifuged fluid onto BacT/Alert MB culture bottles (bioMérieux, Durham, NC).